Controls of solar power systems for grid connected & islanded mode operations. - Ravindran, N.; Kokulavasan, T.; Rajan, R.; Yuvaraj, M.; Ahilan, K.; Atputharajah, A. (University of Jaffna, 2022)
Continuous supply of electricity, when there are supply constrains is a mar challenge. Environmental concerns and nonavailability of fossil fuels increases the demand for the use of renewable energy sources such as solar. A domestic or an institutional customer can support the country by the proper usage of solar Resources. Further the usage of a battery storage combined with the solar panel can improve this. This paper analyses the domestic institutional usage of solar panels, (i) with and (ii) without a battery storage, for both cases of (i) with grid and (ii) standalone operation, depends on the availability of solar irradiation in a day. Here a typical domesticnstitutional solar power system tan into the study and suitable sizes of solar panel, battery storage were selected to achieve a reliable and smooth operation of the system. The whole system is modeled using PSCAD simulation. The design of the controllers ensured the proper operations of grid connected and standalone mode of the system. Further MPPT control also used in such a way to ensure the optimum usage of solar power. The simulation results shows that this arrangement improves the power availability for domestic institutional customers even during the power failure periods.
Keywords: Domestic solar panels; MPPT control; Standalone operation; Payback